Birefringence characterization of injection molded microplates - Adhikari, Achyut (2018)
Birefringence affects the quality of image analysis in injection molded micro-plates. Depending upon their manufacturing / production processes and the type of material, different plates exhibit varying amounts of birefringence. This birefringence is attributed to residual stress generated during the molding process. Polarimeter is the standard tool for birefringence distribution visualization and quantification. Broad chemical resistance and high mechanical stability of the plates are the desirable properties that can be characterized by birefringence measurement. Birefringence, expressed in nm/cm is light retardance (nm) after passing through a sample with certain thickness (cm). Low or uniform birefringence plates provide high-resolution demonstrating higher performance, hence suitable for bio-chemical analysis.